From Agricultural Waste to Functional Tea: Optimized Processing Enhances Bioactive Flavonoid Recovery and Antioxidant Capacity with Multifaceted Health Benefits in Loquat (Eriobotrya japonica Lindl.) Flowers - Mingzheng Duan; Xi Wang; Jinghan Feng; Xu Xiao; Lingying Zhang; Sijiu He; Liya Ma; Xue Wang; Shunqiang Yang; Muhammad Junaid Rao (Horticulturae, 2025)
The large-scale disposal of loquat (Eriobotrya japonica Lindl.) flowers during fruit thinning represents a significant waste of bioactive resources. This study systematically evaluated how three processing methods—fresh (FS), heat-dried (HD), and freeze-dried (FD) treatments—affect the flavonoid composition and antioxidant capacity of loquat flower extracts, with the aim of developing value-added, sugar-free functional tea ingredients. Using UPLC-MS/MS and DPPH assays, we analyzed both pre-(FS/HD/FD) and post-extraction samples (FSP/HDP/FDP) to assess processing-specific metabolic signatures and extraction efficiency. The results revealed that heat-dried powder (HDP) exhibited the highest total flavonoid content and DPPH scavenging capacity (615.24 µg Trolox/g), attributed to enhanced release of stable compounds like quercetin. Freeze-dried powder (FDP) better preserved heat-sensitive flavonoids, such as catechin-(4α→8)-gallocatechin and naringenin, but showed lower overall antioxidant activity. Multivariate analysis confirmed distinct clustering patterns, with heat-drying favoring flavonoid extractability while freeze-drying maintained metabolic diversity. These findings demonstrate that processing methods significantly influence bioactive compound retention and functionality, with heat-drying offering optimal balance between yield and practicality for industrial applications. This work provides a scientific foundation for upcycling loquat flowers into standardized nutraceutical ingredients, addressing both agricultural waste reduction and the growing demand for natural functional foods.